Organic Carbon Dynamics in Soils Amended with Different Organic Manures and Tillage Practices in Rice-Wheat System - Arti Bhatia, Amar Singh, Sudhir Kumar, Y.V. Singh and (Journal of the Indian Society of Soil Science, 2015)
A field experiment was conducted at New Delhi for two years (2006-08) with rice-wheat cropping system to monitor organic carbon dynamics in soils amended with different organic manures under two tillage practices. The experiments included two tillage (puddled and non-puddled in rice and tillage and no-tillage in wheat) practices and seven manuring treatments. Manuring treatments included recommended dose of mineral fertilizer (urea) at 120 kg N ha-1 and combinations of urea with farmyard manure (FYM), green manuring with Sesbania (GM) and municipal solid waste compost (MSW). Soil samples were collected at different crop growth stages from 0-15 and 15-30 cm soil layers. Results showed a significant increase in soil organic carbon (SOC) contents at 0-15 cm after two years of rice-wheat cultivation with application of organic manures and urea. The increase in SOC content was more in non-puddled/ no-tilled under rice-wheat than puddle/tilled conditions of rice-wheat system. Sole organic manures resulted in increased SOC compared to mineral fertilizer alone. Lower soil layers (15-30 cm) showed no significant difference in SOC under different organic manure application. Grain yield of rice and wheat increased when FYM, GM and MSW compost were added with recommended dose of mineral N. The plot with 100% mineral N supplementation with FYM, GM or MSW compost found to increase SOC and yield in soils.